Sustainable Development Goal 16 and Institutional Imperatives: The Role of Judiciary in Nigeria: Array - Ibietan, Jide; Okafor, Stephanie C. (Acta Universitatis Danubius. Administratio, 2020)
This paper discusses the role of institutional frameworks in achieving developmental goals, using Sustainable Development Goal (SDG) 16 which emphasises Peace, Justice and Strong Institutions. The judiciary in Nigeria is construed as being focal or pivotal to the realisation of this goal, hence the paper examines the inherent issues utilising a combination of primary and secondary data backed by descriptive analyses. The paper notes the existence of some institutional frameworks pointing to superficial commitment on the part of central government, but undue executive muzzling vitiates the independence of judiciary, and by its own self-imposed afflictions, the Nigerian judiciary has not demonstrated adequate capacity and readiness to effectively discharge its core functions in attaining this goal. The paper recommends robust capacity building mechanisms that incorporate expertise and professionalism in public bureaucracies, plus multi-stakeholder collaborative approach as platforms for re-invigorating institutions in Nigeria.